Global trends in research of achilles tendon injury/rupture: A bibliometric analysis, 2000–2021 - Wang, Chenguang; Jiang, Zhaohui; Pang, Ran; Zhang, Huafeng; Li, Hui; Li, Zhijun (Frontiers in Surgery, 2023)
Background: The Achilles tendon is the strongest and most susceptible tendon in humans. Achilles tendon injuries and ruptures have gradually attracted research attention. However, a bibliometric analysis of global research in this field is lacking. This study involved a bibliometric analysis of the developmental trends and research hotspots in Achilles tendon injuries/ruptures from 2000–2021. Methods: Articles published between 2001 and 2021 were retrieved from an extended database of the Science Citation Index using Web of Science. VOSviewer and CiteSpace were used to analyze the relationships between publications, countries, institutions, journals, authors, references, and keywords. Results: This study included 3505 studies of 73 countries, 3274 institutions, and 12298 authors and explored the cooperation between them and the relationships between citations. Over the past 22 years, the number of publications has significantly increased. Foot Ankle International has published the most papers on Achilles tendon injuries/ruptures, and British Journal of Sports Medicine is the most famous journal. Re-rupture, exosomes, acute Achilles tendon rupture, and tendon adhesions gradually become the research focus over the past few years. Conclusion: Achilles tendon injury and rupture are important research topics. A vast number of newly published papers on this topic have demonstrated that clinicians and researchers are interested in their study. Over time, these recent studies will be widely cited; therefore, this bibliometric analysis should be constantly updated.